2018
DOI: 10.1088/1361-6463/aadde7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the electrochemical reaction mechanism of VS2 nanosheets in lithium-ion cells by multiple in situ and ex situ x-ray spectroscopy

Abstract: Recently two-dimensional layered transition metal dichalcogenides (TMDs) have attracted great scientific interest in electrochemical energy storage research. Vanadium disulfide (VS2) as an important family member of TMDs, is a promising electrode material for lithium-ion cells because of its remarkable electrical conductivity and fast Li + diffusion rate, but its electrochemical reaction mechanism is still poorly understood. Herein, we have prepared VS2 nanosheets as the electrode and systematically investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
1
19
1
Order By: Relevance
“…Those two cathodic peaks are ascribed to the phase transition during the Li + intercalation process from VS 2 to Li x VS 2 [24] . For the anodic scan, the oxidation peak in the initial cycle can be assigned to the Li + deintercalation process and the phase was transformed from Li x VS 2 to VS 2 [9,52] . It is noted that there was a weak reduction peak at 2.1 V in the second cathodic scan, which may be connected with the phase change of VS 2 during the lithium intercalation [52] .…”
Section: Resultsmentioning
confidence: 99%
“…Those two cathodic peaks are ascribed to the phase transition during the Li + intercalation process from VS 2 to Li x VS 2 [24] . For the anodic scan, the oxidation peak in the initial cycle can be assigned to the Li + deintercalation process and the phase was transformed from Li x VS 2 to VS 2 [9,52] . It is noted that there was a weak reduction peak at 2.1 V in the second cathodic scan, which may be connected with the phase change of VS 2 during the lithium intercalation [52] .…”
Section: Resultsmentioning
confidence: 99%
“…[115] For thinner VS 2 flakes, the Li + intercalation process was reversible, whereas the conversion reaction was not fully reversible in the charging process, during which part of Li 2 Sw as oxidized to S 8 with excess V. Zhang et al also found as imilarL i + storagep rocess based on the analysiso f in situ and ex situ XASr esults;t he hybridization strengthb etween Sa nd Vs trongly depended on the states of charge, and the solid-electrolyte interface (SEI) film dynamically evolved during cycling ( Figure 14 a-f 2 ). [136] Meanwhile, the VS 2 electrode also demonstrated the Li + storage mechanism of the intercalation reaction between 0.5 and 3.0 Vw ith the occurrence of a complexp hase transition for ASSLIBs (Figure 14 g). [47] Similar to other electrode materials in SCs, VS 2 materiale xhibits the electrochemical reactionm echanism of surfacee lectroadsorption with capacitance as the predominant Li + storagep rocess; pseudocapacitive behavior with weak intercalation has also been probed.…”
Section: Experimentally Determined Metal-ion Storage Mechanismmentioning
confidence: 96%
“…Reproducedw ith permission. [136] Copyright 2018, IOP Science.g )Schematic illustration of the ASSLIB. Reproduced with permission.…”
Section: Experimentally Determined Metal-ion Storage Mechanismmentioning
confidence: 99%
See 2 more Smart Citations